Does internal control and firm-specific characteristics impact firm value? an empirical investigation on Indian manufacturing sector / Anju Kalluvelil Janardhanan - Kalluvelil Janardhanan, Anju (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This research aims to investigate the role of firm-specific characteristics (firm size, firm age, liquidity, firm complexity, board independence, institutional ownership, annual volatility of stock returns, leverage) and internal control (Enterprise Risk Management, Big4 auditor) on firm value (Tobin’s Q, Return on Equity, Return on Assets). The proposition was addressed with a sound statistical investigation of 60 companies listed in the NSE India manufacturing sector by utilising annual panel data for 11 years from 2007-17. The findings of this study imply that there is variation in firm value (Q) due to the adoption of ERM and Big4. On the other side, there is no difference in firm value measured by ROA and ROE. Regression analysis revealed that the adoption of ERM, firm size, firm age and liquidity influenced Q. The study found that ROA was impacted by ERM, firm size, firm age, firm complexity, liquidity and leverage. Findings also show that firm size, firm complexity, liquidity and leverage affected ROE. This empirical investigation is an addition to the existing extant literature available on firm value as it identifies the determinants from a three-dimensional perspective- purchasers, management, investors and are of particular interest to investors, researchers and managers.